Effect of different dielectrics on material removal rate, electrode wear rate and microstructures in EDM - Niamat, Misbah; Sarfraz, Shoaib; Aziz, Haris; Jahanzaib, Mirza; Shehab, Essam; Ahmad, Wasim; Hussain, Salman (Elsevier, 2017)
Diesinker electric discharge machining is widely used non-conventional technique for making high precision and complex shaped parts. Dielectrics and electrical parameters were considered as the main factors for EDM performance. In this paper, the effects of pulse-on-time (μs) and current (ampere) were evaluated for performance measures using kerosene and water as dielectrics. A comparison was performed for both dielectrics in terms of material removal rate (mm3/min), electrode wear rate (mm3/min), and microstructures. Aluminum 6061 T6 alloy was used as material for this research due to its extensive use in aerospace and automotive industries. Experiments were designed using Taguchi L9 orthogonal array (OA). Time series graphs were plotted to compare material removal rate and electrode wear rate. Microstructures were taken by scanning electron microscope to analyze the surface produced in terms of cracks, globules and micro-holes. Higher material removal rate and lower electrode wear were achieved with kerosene dielectric. The novelty of this research work, apart from its practical application, is that Aluminum 6061 T6 alloy is used as work material to compare the performance of dielectrics (kerosene and distilled water). Paper presented at: Complex Systems Engineering and Development Proceedings of the 27th CIRP Design Conference Cranfield University, UK 10th – 12th May 2017.
Keywords: Electric Discharge Machining; Material Removal Rate; Electrode Wear Rate; Dielectric; Microstructures